On some deep-sea Stenheliinae from the Gulf of California and the west coast of the Baja California Peninsula (Mexico): the genus Delavalia Brady, 1869 and proposal of Archaeohuysia gen. nov. and Diarthropodella gen. nov. (Copepoda: Harpacticoida: Miraciidae) - Gómez, Samuel (Zootaxa, 2021)
Several species belonging to the harpacticoid families Ameiridae Boeck, Ancorabolidae Sars, Argestidae Por, and Rhizothrichidae Por have been described so far as an ongoing long-term project on the diversity of deep-sea benthic harpacticoids collected from the Gulf of California and Mexican Pacific. Amongst the several harpacticoid taxa, the subfamily Stenheliinae Brady (Miraciidae Dana) showed to be one of the most important components to overall species richness in deep-sea sediments. Following the rejection of segmentation pattern of the first swimming leg as the only discriminant for subgeneric assignment of stenheliin taxa, four new species of Delavalia Brady, 1869 and two new genera, Archaeohuysia gen. nov. and Diarthropodella gen. nov. are proposed herein. The new Delavalia species belong to the longicaudata-group with close relatives in shallow-water habitats. The so far monotypic Archaeohuysia gen. nov. showed to be unique in the combination of the general structure of the first swimming leg and retention of the primitive complement of four setae on the second endopodal segment of the same leg. Diarthropodella gen. nov. is the only stenheliin taxon with a two-segmented exopod of the first swimming leg. Some comments are given on probable multiple colonization events of stenheliin taxa.